2017
DOI: 10.1159/000478628
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis and the Hydrogen Sulfide Signaling Pathway – Therapeutic Approaches to Disease Prevention

Abstract: Hydrogen sulfide (H2S) is now admitted as a third gasotransmitter together with nitric oxide (NO) and carbon monoxide (CO), albeit it was originally considered as a foul and poisonous gas. Endogenous H2S production in mammalian cells is counting on the three enzymes acting on cysteine. Involvement of H2S in various physiological and pathological processes has been extensively studied in the last fifteen years. Mounting evidence suggests that H2S is able to protect ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 135 publications
(132 reference statements)
0
17
0
Order By: Relevance
“…The anti-atherosclerotic mechanisms of H 2 S have been gradually described, including anti-inflammatory response, anti-oxidative action, endothelial function preservation, inhibition of foam cell formation and regulation of ion channels (Altaany et al, 2014;Mani et al, 2014;Xu et al, 2014;Wang et al, 2017;Barton and Meyer, 2019). Reduced CSE expressions at both mRNA and protein levels are detected in ox-LDL-treated endothelial cells and in aortas from apolipoprotein E knockout (ApoE -/-) mice (Leucker et al, 2017).…”
Section: H 2 S-related Endothelial Dysfunction In Atherosclerosismentioning
confidence: 99%
“…The anti-atherosclerotic mechanisms of H 2 S have been gradually described, including anti-inflammatory response, anti-oxidative action, endothelial function preservation, inhibition of foam cell formation and regulation of ion channels (Altaany et al, 2014;Mani et al, 2014;Xu et al, 2014;Wang et al, 2017;Barton and Meyer, 2019). Reduced CSE expressions at both mRNA and protein levels are detected in ox-LDL-treated endothelial cells and in aortas from apolipoprotein E knockout (ApoE -/-) mice (Leucker et al, 2017).…”
Section: H 2 S-related Endothelial Dysfunction In Atherosclerosismentioning
confidence: 99%
“… [96] also demonstrated that decreased endogenous H 2 S generation accelerated AS in CSE-knockout mice. Accumulating evidence [97] , [98] has shown that endogenous H 2 S produced by CSE in blood vessels has an anti-AS effect. Unstable plaques generated by AS are prone to rupture and have the risk of infarction [99] .…”
Section: Pathophysiological Regulation Of H 2 S Onmentioning
confidence: 99%
“…This observation is also supported by a study on the ApoE −/− mice consuming high-fat diet, showing that H 2 S may inhibit the atheromatous lesions progression, by regulating the expression of CX3CR1 and C-X3-C CX3CL1, in atheromatous plaques macrophages. However, the H 2 S antiatheromatous action may involve several mechanisms, such as vasorelaxation, endothelium preservation, anti-inflammatory responses, and the regulation of ion channels or antioxidative action (33), so further research is necessary to ensure validation.…”
Section: Pvat and Atherosclerosismentioning
confidence: 99%